2022
DOI: 10.1021/acssynbio.1c00554
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Green- and Red-Fluorescent Reporter Proteins Based on the Fluorescence-Activating and Absorption-Shifting Tag for Use in Acetogenic and Solventogenic Anaerobes

Abstract: Anaerobic bacteria are promising biocatalysts to produce industrially relevant products from nonfood feedstocks. Several anaerobes are genetically accessible, and various molecular tools for metabolic engineering are available. Still, the use of bright fluorescent reporters, which are commonly used in molecular biological approaches is limited under anaerobic conditions. Therefore, the establishment of different anaerobic fluorescent reporter proteins is of great interest. Here, we present the establishment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 58 publications
(91 reference statements)
0
17
0
Order By: Relevance
“…Further factors to contribute to culture heterogeneity are cell morphogenesis or sporulation, both of which are especially apparent in clostridial cultures (Jones et al 2008;Tracy et al 2010). Most recently, Flaiz et al (2022) also demonstrated heterogeneity of C. saccharoperbutylacetonicum cultures expressing feg in a P tcdB -dependent manner with tcdR controlled by P bgaL . Again, culture heterogeneity was observed throughout all growth phases, although in this case, the number of fluorescent cells was higher compared to the present study (Flaiz et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Further factors to contribute to culture heterogeneity are cell morphogenesis or sporulation, both of which are especially apparent in clostridial cultures (Jones et al 2008;Tracy et al 2010). Most recently, Flaiz et al (2022) also demonstrated heterogeneity of C. saccharoperbutylacetonicum cultures expressing feg in a P tcdB -dependent manner with tcdR controlled by P bgaL . Again, culture heterogeneity was observed throughout all growth phases, although in this case, the number of fluorescent cells was higher compared to the present study (Flaiz et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For example, FAST:HMBR fluorescence of anaerobic Clostridium organisms was monitored aerobically using confocal microscopy, microplate reader measurements and flow cytometry measurements (21). Another recent study applied flow cytometry (aerobic) to detect fluorescence of anaerobic, acetogenic bacteria (29). Other studies avoid oxygen when detecting FAST:fluorogen fluorescence of anaerobic organisms, e.g., by placing a fluorescence microscope or microplate reader into anaerobic chambers (14, 30).…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study applied flow cytometry (aerobic) to detect fluorescence of anaerobic, acetogenic bacteria (29). Other studies avoid oxygen when detecting FAST:fluorogen fluorescence of anaerobic organisms, e.g., by placing a fluorescence microscope or microplate reader into anaerobic chambers (14,30).…”
Section: Aerobic Vs Anaerobic Detection Of Fast:fluorogen Fluorescencementioning
confidence: 99%
“…This behavior had been previously described only in fixed embryo or in live embryos analyzed by label-free nonlinear microscopy, but these techniques did not give access to the individual phases of the cell cycle. GreenFAST and redFAST were recently used as fluorescent reporters for investigating the coculture dynamics of metabolically engineered Clostridium saccharoperbutylacetonicum strains under anaerobic conditions …”
Section: The Growing Family Of Fast Reportersmentioning
confidence: 99%
“…GreenFAST and redFAST were recently used as fluorescent reporters for investigating the coculture dynamics of metabolically engineered Clostridium saccharoperbutylacetonicum strains under anaerobic conditions. 40 ■ FAST-BASED SENSORS Topological variants of FAST were developed to design fluorescent chemogenetic biosensors (Figure 5). The possibility to condition fluorogen binding, and thus fluorescence, to a given recognition event or cellular signal enabled the development of sensors for various applications in biological research.…”
Section: ■ the Growing Family Of Fast Reportersmentioning
confidence: 99%